PROIECȚIA COGNITIVĂ A NEOLOGISMELOR INTERNAȚIONALE ÎN CONTEXTUL EVOLUȚIILOR ACTUALE - Molea, Viorica (ProLibra, 2022)
The new circumstances of society’s development entails the acquisition of new words and expressions that reflect these realities. It is a only natural that all the changes occuring in the world have an echo in the language, in general. And, since these changes can be downright overwhelming, they are all reflected in the lexicon and in communication. At the same time, we should mention that some linguistic areas have a greater impact on new lexical acquisitions than others. But, whatever the trends in this regard, there is a progressive growth of international neological elements, and, through them, a standardization of perceptions, of thinking in the immense space of human civilization. We note that the investigation of trends related to the ever closer interpenetration of languages through the use of an international neological lexicon constitutes an ongoing objective in linguistic research.
The Cognitive Projection of International Neologisms in the Context of the Current Developments
MOLEA, Viorica. Proiecția cognitivă a neologismelor internaționale în contextul evoluțiilor actuale. In: Filologia modernă: realizări şi perspective în context european : Institutul de Filologie Română „Bogdan Petriceicu-Hasdeu”: 65 de ani de la fondare: conferinta științifică internațională, ediția a 16-a, 20-22 octombrie 2022, Chişinău. Chişinău: Pro Libra, 2022, pp. 103-107.
Keywords: neologisme internaționale; globalizare